STRANGE BEDFELLOWS: UNITED STATES UNIFORMED SERVICES AND INFECTIOUS DISEASE. - Bacon, Jeffrey. (Tufts University. Tisch Library., 2019)
Infectious disease outbreaks represent a fascinating problem for the discipline of security studies. Infectious disease outbreaks are evolving as a nontraditional, global threat because it they are unique among natural disasters. The purpose of the study is to build upon existing pandemic management policy and security studies theory to improve future response efforts to infectious disease crises and to improve the reader's understanding of how to effectively utilize all of the United States (U.S.) Government's capabilities and equities in response to future infectious disease outbreaks. Specifically, how does the use of U.S. uniformed services, to include the armed forces, affect the success of a response to an infectious disease crisis? This study examines two seminal infectious disease outbreaks to include the 1918-19 H1N1 Influenza pandemic and the 2014-16 Ebola Virus Disease (EVD) epidemic using the comparative historical methodologies. Activities conducted by the uniformed services across five response domains were interrogated to include: Incident Management; Surveillance and Epidemiology; Laboratory Network and Diagnostics; Medical Care and Countermeasures; and Community Mitigation. The analysis reveals that the uniformed services have an important legacy in matters of public health and offer unique capabilities in response to this distinct form of natural disaster. Surveillance and Epidemiology and Medical Care and Countermeasures require improvement and additional policy analysis. Incident Management, Laboratory Network and Diagnostics, and Community Mitigation require continued refinement and sustainment. The success of all uniformed services' activities is found to be linked to a support relationship directed by host-nation civilian authorities. Generalizations from this analysis can be made, with caution, for nations suffering from conflict/post-conflict environments, having a history of external interventions, and that enjoy a special relationship to the U.S. This analysis seeks to contribute to the body of literature and debate regarding the securitization of health. Further empirical analysis of the uniformed services' unique contributions is recommended to inform this important field and to advance the global health security agenda.; Thesis (Ph.D.)--Tufts University, 2019.; Submitted to the Dept. of Diplomacy, History, and Politics.; Advisor: Robert Pfaltzgraff.; Committee: Ian Johnstone, and Nahid Bhadelia.; Keywords: International relations, Military studies, and Health sciences.